2-D Electrical Resistivity Tomography for the Assessment of Seawater Intrusion, around Okerenkoko Island, Delta State, Nigeria - SIKIRU, Jamiu; JIMOH, Caeser (WATER RESOURCES JOURNAL, 2025)
A 2-D Electrical Resistivity Tomography investigation was carried out to assess the probable cause of the non-potability of groundwater resources at the Okerenkoko coastal community, located along the Escravos River, Niger Delta. The Wenner Electrical resistivity configuration was used in data acquisition with electrode spacing ranging between 3 to 5 m, and a total of four readings was collected per traverse, where n=3, 6, 9, and 12 m; as well as n=5, 10, 15 and 20 m. Five (5) traverses were covered as follows; Traverse 1, Jetty Area covering a total distance of 144 m at a depth of 14.4 m; Traverse 2, Zion Area covering a total distance of 144 m with 7.46 m depth; Traverse 6, Chief Dennis Area covering a total distance of 400 m with 12.4 m depth; Traverse 5, Assemblies of God Area covering a total distance of 240 m with a 12.4 m depth, and Traverse 8, Debama-Azama Area covering a total distance of 144 m with a depth of 7.46 m respectively. Seawater intrusion was interpreted along; Traverse 6, 5, 2, and 1, with the following electrical resistivity values: 0.656-2.10 Ùm, 1-2.35 Ùm, 0.09-0.30 Ùm, and lastly 0.61-3.06 Ùm respectively. From our findings, we conclude that; areas around waterfront or coastline are more susceptible to seawater intrusion than those far away. We suggest that; water boreholes should be sited landward and drilled to at least a depth of 200 m and properly grouted to prevent seawater intrusion at shallow depths which might cause public health disorders.
NIL
This article is the outcome of our findings on Seawater Intrusion around Okerenkoko.
Keywords: Seawater Intrusion; Escravos River; 2-D Electrical Resistivity Tomography; Public Health.